Valuing jazz: cross-cultural comparisons of the classical influence in jazz - Williams, Katherine A. (2012)
‘Valuing Jazz: Cross-cultural Comparisons of the Classical Influence in Jazz’ re-examines the interaction of Western classical music and jazz, focussing particularly on developments in North America and Britain in the twentieth century. This dissertation acknowledges and builds on the existing connections that have been drawn between classical music and jazz—both those that underscore the musical differences between the two idioms in order to discredit the latter, and those that acknowledge similarities in order to claim cultural legitimacy for jazz. These existing studies almost universally use outdated evaluative criteria, and I seek to redress this by using contemporary classical-music practices and discourses as my point of reference. By adopting a range of methodologies to investigate both intra- and extra-musical trends, this dissertation offers a thorough and balanced exploration of the topic.